Relationship between factors and the adequacy of the Singapore Central Provident Fund (CPF) to meet post retirement consumption - Toh, Jia De (2009)
Singapore like many developed countries is gradually transforming into an ageing population. With indications of an increasing need for retirees to support themselves after retirement, this report is set forth to determine and analyze the variables that affect the adequacy of the CPF scheme in meeting the post retirement consumption expenditure. A hypothetical scenario is set up to study the impact of the variables on the CPF retirement balance of an average Singaporean individual. Sensitivity analysis, regression and adequacy test were run on secondary data and statistics. Our findings have shown that both CPF interest rate and CPF contribution rate have a strong positive impact on the retirement balance at one’s retirement age, with CPF interest rate being more efficient in determining and adjusting the adequacy of the CPF interest rate. However inflation worsens the ability of the individual to meet his consumption expenditure at 60% replacement ratio.